Export assistance in overcoming export barriers : Case: Contact-facilitating group export project of Finnish SMEs towards the Japanese market - Sorvari, Milja (My University, 2022)
Small and medium sized enterprises (SMEs) are crucially important to national economies, and international markets, especially exports, offer great growth opportunities for the SMEs. However, SMEs face various barriers in exporting which hinder their exporting activities. Export assistance can serve as an external support to complement and develop the resources and capabilities of a firm which will enable a better success in the export markets. High context specificness and a broad variety of export assistance measures impose a need to examine different types of export assistance in more depth to understand how the provided support effects and helps SMEs. The main research question of this study is: “How can export assistance programs help SMEs overcome barriers in exporting?”. To answer the question, this research explores a contact-facilitating group export project of Finnish SMEs towards the Japanese market. This research was conducted as qualitative case study. The empirical data was collected mainly through interviews with company representatives from the SMEs who participated in the contact-facilitating group export project. The theoretical background of this study builds on export barrier, export assistance and export performance literature as well as the resource-based view of the firm. The theoretical framework is based on existing theory and is used to understand the complex indirect effect of export assistance on SMEs who receive it. This study found that contact-facilitating export assistance in the form of a group export project can help lower barriers related to language, culture and business practice differences, contacting and establishing relationships with business partners, lack of knowledge of the target market and its opportunities, and managerial, financial and human resource barriers. These barriers can be targeted through a combination of informational and experiential knowledge measures which develop the export-related resources and capabilities. Also financial support plays a big part in enabling the participation to export assistance programs and motivating managers to export. One of the greatest value creating aspects of the export assistance case of this study was the group project approach were the SMEs benefitted especially from the peer group network in terms of knowledge sharing. A contact-facilitating group export assistance was found to best support SMEs who are experienced exporters with a limited scope.

Pienet ja keskisuuret yritykset (pk-yritykset) ovat elintärkeitä kansantalouksille. Kansainväliset markkinat ja erityisesti vienti tarjoavat merkittäviä kasvumahdollisuuksia pk-yrityksille. Pk-yritykset kohtaavat kuitenkin erilaisia viennin esteitä, jotka vaikeuttavat vientitoimintaa. Vientituki voi ulkoisena apuna täydentää ja kehittää yrityksen resursseja ja kyvykkyyksiä, jotka mahdollistavat paremman onnistumisen vientimarkkinoilla. Laaja valikoima erilaisia vientituen menetelmiä ja kontekstin merkityksellisyys korostavat tarvetta tutkia eri vientitukimenetelmiä tarkemmin, jotta voidaan ymmärtää miten annetut tuet auttavat pk-yrityksiä. Tämän tutkimuksen päätutkimuskysymys on: “Miten vientitukiohjelmat auttavat pk-yrityksiä ylittämään viennin esteitä?”. Vastatakseen tähän kysymykseen, tämä tutkimus tarkastelee vientiprojektia yritysryhmälle, jonka tarkoituksena on ollut fasilitoida suomalaisten pk-yritysten kontaktien luomista Japanin markkinoilla. Tutkimus toteutettiin kvalitatiivisena tapaustutkimuksena. Tutkimuksen empiirinen data on pääasiassa kerätty haastatteluilla vientiprojektiin osallistuneiden pk-yritysten edustajien kanssa. Tutkimuksen teoreettinen tausta pohjautuu viennin esteiden, vientituen, viennin tuloksellisuuden sekä resurssiperusteiseen teoriaan. Teoreettinen viitekehys on rakennettu olemassa olevan tutkimuksen pohjalta, ja sen tarkoituksena on auttaa muodostamaan ymmärrys vientituen monitahoisesta ja epäsuorasta vaikutuksesta sitä saaviin pk-yrityksiin. Tutkimuksen tulokset osoittavat, että kontaktien luomisen fasilitointiin tähtäävä vientitukiprojekti voi alentaa viennin esteitä liittyen kielen, kulttuurin ja liiketapojen erilaisuuteen, kontaktointiin ja suhteiden luomiseen mahdollisten kauppakumppaneiden kanssa, kohdemarkkinan ymmärryksen puutteeseen, sekä johdon, talouden sekä henkilöstön resurssinäkökulmiin. Näitä esteitä voidaan alentaa erilaisilla toimenpiteillä, jotka yhdistelevät informaation ja kokemuksien kerryttämisen keinoja. Myös taloudellinen tuki on merkittävä, sillä se usein mahdollistaa vientitukiohjelmiin osallistumisen ja motivoi yritysjohtoa vientitoimiin. Yksi keskeisimmistä arvoa luovista näkökulmista vientituessa oli se, että projekti tehtiin ryhmässä, jolloin pk-yritykset hyötyivät erityisesti ryhmän sisäisen verkoston tiedonjaosta. Kontaktien luomisen fasilitointiin tähtäävä vientiprojekti yritysryhmälle sopii parhaiten pk-yrityksille, jotka ovat rajallisesti kokeneita viennin saralla.
Keywords: Export assistance, contact-facilitating export assistance, group export project